Tumultuous years : the Presidency of Harry S. Truman, 1949-1953 - Donovan, Robert J. (Columbia : University of Missouri Press, 1996)
"Originally published: New York: Norton, c1982."
Keywords: Presidents -- United States. -- Biography; Truman, Harry S., 1884-1972.; United States -- Foreign relations -- 1945-1953.; United States -- Politics and government -- 1945-1953.